Rhetorical Analysis of Gus Baha's Da'wah in the Perspective of Islamic Education (Study of the Qur'an, Surah An-Nahl Verse 125) - Adha Mubarok; Muhajir; Ilzamudin Ma’mur; Wasehudin; Fandi Adpen (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Education is a very important matter in Islam. If this education cannot be implemented well and perfectly, then physical, emotional, spiritual and intellectual balance will become unstable. Da'wah is an important indicator to measure the level of teacher involvement in implementing the Islamic Education Philosophy and State Education Philosophy. There are various approaches and methods in carrying out the da'wah process that can be implemented by Islamic education teachers. Education is also one of the da'wah methods to convey understanding about the teachings of the Islamic religion. If all Islamic education teachers have the knowledge and understanding of how to use da'wah methods correctly, then it is certain that the Islamic Education Philosophy and State Education Philosophy can be achieved well. There is one of the ulama who is on the rise, namely Gus Baha, whose preaching rhetoric can be used as a reference for use in teaching Islamic education.